Karya Seni “Stamp Painting” Bahan Alam Upaya Menstimulasi Kecerdasan Naturalis AUD Usia 4-5 Tahun - Pratiwi, Shelly; Sopiah, Sopiah (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
This study was motivated by the issue of insufficient stimulation of naturalistic intelligence among children aged 4–5 years at Kober Majasari 1 Cibiuk. The purpose of this research was to enhance the naturalistic intelligence of children aged 4–5 years at Kober Majasari 1 Cibiuk through art activities using “stamp painting” with natural materials. This study employed a classroom action research (CAR) method consisting of two cycles. Each cycle included planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation. The subjects of the study were 2 teachers and 13 students, consisting of 8 boys and 5 girls. The results showed that natural-material-based “stamp painting” activities were able to stimulate children’s naturalistic intelligence, as indicated by improvements in their ability to recognize, understand, and interact with their surrounding environment. This was reflected in a success rate of 46%. In the second meeting of Cycle I, children’s naturalistic intelligence increased by 15%, reaching a success rate of 61%. In the first meeting of Cycle II, naturalistic intelligence showed a greater improvement of 24%, reaching 85%. In the second meeting of Cycle II, naturalistic intelligence increased by a further 7%, rising from 85% to 93%. This study is expected to contribute to the development of art-based learning in early childhood education, particularly in stimulating children’s naturalistic intelligence.  Keywords: Stamp Painting, Naturalistic Intelligence, Early Childhood